The Beauty and The Abuse: A handbook on relationships and emotions in academia - Nigel Morgan (Creative Commons. CC BY-NC-ND Women Academics in Tourism, Copenhagen, 2017)
This handbook encourages dialogue and reflexivity on human relationships and emotions in academic environments. Fifteen vignettes inspired by real stories are presented. These narratives explore the light and shade of how love, friendship, eroticism, power, sexism, harassment andgendered academic identities and cultures shape our daily working lives. This intervention tool has been designed to be used in workshops, seminars and other forms of academic gatherings. It can also be used and shared freely for information and inspiration among individual academics, in mentoring programs and as an input for competence development of academic leaders and managers. The document includes reflexive questions, a workshop pedagogy and a thematic list of recommended resources.